AD.0004

Упростите выражение:

      (4b² + 2a² — 4ab) * (3ab + 2a² — 3b³).

   Раскроем скобки, умножив трехчлены:

      Z = (4b² + 2a² — 4ab) * (3ab + 2a² — 3b³);

      Z = 4b² * (3ab + 2a² — 3b³) + 2a² * (3ab + 2a² — 3b³) — 4ab * (3ab + 2a² — 3b³);

      Z = (4b² * 3ab + 4b² * 2a² — 4b² * 3b³) + (2a² * 3ab + 2a² *2a² — 2a² * 3b³) — (4ab * 3ab + 4ab * 2a² — 4ab * 3b³);

      Z = 12ab³ + 8a²b² — 12b5 + 6a³b + 4a4 — 6a²b³ — 12a²b² — 8a³b + 12ab4;

   Приведем подобные члены:

      Z = 12ab³ — 4a²b² — 12b5 — 2a³b + 4a4 — 6a²b³ + 12ab4.

Добавить комментарий

Ваш адрес email не будет опубликован.